1999
DOI: 10.1074/jbc.274.9.5666
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Human Peroxisomal Targeting Signal Receptor PEX5

Abstract: Import of matrix proteins into peroxisomes requires two targeting signal-specific import receptors, Pex5p and Pex7p, and their binding partners at the peroxisomal membrane, Pex13p and Pex14p. Several constructs of human PEX5 have been overexpressed and purified by affinity chromatography in order to determine functionally important interactions and provide initial structural information. Sizing chromatography and electron microscopy suggest that the two isoforms of the human PTS1 receptor, PEX5L and PEX5S, for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
83
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(92 citation statements)
references
References 34 publications
7
83
1
Order By: Relevance
“…The purified preparation of Pex5p exhibited a major band of approximately 80 kDa on SDS-PAGE (Fig. 1A), being consistent with a previous report (23). Minor bands were seen in the lower molecular weight region.…”
Section: Purification Of Recombinant Proteins-humansupporting
confidence: 79%
“…The purified preparation of Pex5p exhibited a major band of approximately 80 kDa on SDS-PAGE (Fig. 1A), being consistent with a previous report (23). Minor bands were seen in the lower molecular weight region.…”
Section: Purification Of Recombinant Proteins-humansupporting
confidence: 79%
“…Presently, our knowledge on the structure/function of amino acid residues 118 -639 of mammalian Pex5p is quite vast. Indeed, a variety of biochemical and structural studies have shown that this region of the protein contains the binding site for PTS1-containing cargo proteins (7,(22)(23)(24)(25)(26)(27), seven Pex14p-binding domains (43)(44)(45), and binding sites for Pex7p (11)(12)(13)(14), Pex12p (46), and Pex13p (45). In sharp contrast, not much is known regarding the role of the first 117 amino acid residues of Pex5p.…”
Section: Pex5p Lacking the First 110 Amino Acid Residues Is Efficientmentioning
confidence: 99%
“…Pex5p recognizes matrix proteins via their C-terminal tripeptide motif (PTS1); Pex7p recognizes an N-terminally located amino acid motif (PTS2). The main components onto which cargo and receptors dock are Pex13p (an integral peroxisomal membrane protein) and Pex14p (a peroxisomal membrane-associated protein), as established by a combination of techniques: yeast two-hybrid interactions, co-immunoprecipitations and, recently, surface plasmon resonance analysis using purified proteins 9,22 . Well-defined (sub)domains exist in many of the Pex proteins (peroxins) for which the three-dimensional structure is known from other protein family members (see Table 1).…”
Section: Figurementioning
confidence: 99%